Drought and Salinity Stress Responses in Wheat (Triticum aestivum L.): Activation of Antioxidative Defense and Accumulation of Stress Responsive Metabolites - Pradhan, B.; Chakraborty, U. (International Journal of Bio-resource and Stress Management, 2013)
Nine different wheat (Triticum aestivum L.) varieties- Mohan Wonder (MW), Kedar (KD), Gayetri (GY), Gandhari (GN), Kaweri (KW), PBW 343, UP 2752, Sonalika (SO), LV were subjected to drought stress for 3, 6 and 9 days and salt stress of 50 mM, 100 mM and 200 mM. A general decrease was seen in the activity of catalase and superoxide dismutase during both stresses in MW, GY, LV and SO whereas there was an initial enhancement in case of other cultivars. The activities of peroxidase and glutathione reductase showed a general increase in case of all varieties following drought and salt stress respectively but the later stages showed a decrease in case of MW, GY, LV and SO with the increase in the duration of stress. Ascorbate peroxidase showed a steep rise in its activity with the onset of stress followed by a decline when the duration and severity of stress increased. There was an increase in the accumulation of H2O2, lipid peroxidation and decrease in MSI in case of MW, GY, and LV and SO in the leaf following stress and a concentration dependent increase in H2O2 staining was observed in the leaf evident as brown coloured spots due to DAB polymerization in the stressed leaf in comparison with the control plants. Proline, total carbohydrates, starch, phenol and ascorbate content increased with increase in the period of water stress. The accumulation of total antioxidant and carotenoid showed an initial enhancement whereas total chlorophylls showed a general decline during water stress. Results of the present study indicate that out of the nine tested cultivars- KD, GN, KW showed the highest tolerance to the stress followed by PBW 343, UP 2752 and the other four showed were susceptible to drought and salinity stress.